Mediation effects of behavior outcomes in the relationships between human resource practices and firm performance - Babaei, Davood (2011)
In this study the researcher examined the relationships between human resource practices (HRPs), firm performance (service quality), and the mediation effects of employees’ behavior outcomes including organizational citizenship behaviors (OCBs), employees’ abilities and employees’ motivation. The HRP studied included job description, selection, training, reward, career development, job security, performance appraisal, and participation practices. Data were collected from a sample of 104 branches of a public bank and 75 branches of a private bank from two Iranian banks located in Tehran, the capital city of Iran. From each branch, three personnel (a manager or an assistant manager and two non-managerial employees) and five customers served as the source of the data. A total of 167 managers or assistant managers, 253 non-managerial employees, and 781 customers participated in this study. The study takes the branch as the unit of analysis, rather than the customers or bank personnel. To test this mediation model and examine if the hypothesized model fit the data, Structural Equation Modeling (SEM) analysis was used. To assess the relationships among variables, before evaluating the fit of the structural model, the researcher defined measurement model to verify that the measurement variables used to reflect the unobserved constructs do so in a reliable manner. SEM was utilized to test the fitness of the model and to provide evidence of discriminate validity through chi-square difference tests. Amos 16.0 (SPSS Inc., 2009) was used to analyse the measurement model and structural model for the direct and indirect relationships between HRP and firm performance; including employees’ behaviour outcome variables as mediator variables. The results showed that OCBs and employees’ motivation fully mediated the relationship between reward practices and firm performance. It was further realized that OCBs and employees’ abilities partially mediated the relationship between performance appraisal practices and firm performance. The study revealed that employees’ abilities and motivation partially mediated the relationship between participation practices and firm performance. Further, the result showed training practices had an indirect significant relationship with firm performance through employees’ abilities. The career development practices were found to have had an indirect significant relationship with firm performance through employees’ motivation in this study. However, the results showed that in this examined model, job description, selection and job security did not have any significant effect on employees’ behavior outcome variables and firm performance. To identify differences in firm performance between the private and the public Iranian banks the independent-samples t test analysis was used. The results of the test indicated that there was no significant difference in firm performance between private and public banks in Iran. Overall, this study provides a more comprehensive understanding of the role of human resource practices in increasing firm performance. The findings of the current study provided insights into the role of HRPs, OCBs, employees’ ability, and employees’ motivation in firm performance. Furthermore, it becomes important for organizations to build strategic practices in terms of training, career development, reward, participation, and performance appraisal. Hence, organizations need to focus on improving their human resource practices, thereby, enhancing employees’ ability and motivation and firm performance. Therefore, under such good practices, a benign cycle will be formed which promotes the employees’ behavior outcome variables of employees to improve firm performance in terms of service quality Item Type: Thesis (PhD)